Wetted front advance under subsurface vertical line segment source - VERMA, CHHEDI LAL; PANDEY, RAVI KANT; RICHA, SUSHRUT; MISHRA, SHYAMJI (Journal of Soil and Water Conservation, 2025)
Subsurface vertical line segment source is suitable for applying irrigation water to deep rooted plantations. Wetted front advance in horizontal and vertical direction are required for deciding the spacing between emitters and drip laterals. Shape of wetted soil mass in combination of average change in volumetric moisture content as single simple soil input parameter may leads to development of simple models for predicting wetted front advance. In the present study a mathematical model known as Effective Spheroid Model has been developed to describe wetted front advance under subsurface vertical line source flow geometry. The developed model was tested with experimental sand tank model data especially for lateral and vertical advances of wetted fronts. The values of predicted wetted front radii and depths compared closely with the observed wetted front radii and depths with average percent deviations of 5.74% and 12.02%, respectively once the flow geometry is fully developed. Advantage of the model is that it requires average change in volumetric moisture content as single soil input parameter, which is quite easy to determine under field conditions. The developed model may be satisfactorily used for field application.